2007
DOI: 10.1073/pnas.0706481104
|View full text |Cite
|
Sign up to set email alerts
|

Leptin replacement alters brain response to food cues in genetically leptin-deficient adults

Abstract: A missense mutation in the ob gene causes leptin deficiency and morbid obesity. Leptin replacement to three adults with this mutation normalized body weight and eating behavior. Because the neural circuits mediating these changes were unknown, we paired functional magnetic resonance imaging (fMRI) with presentation of food cues to these subjects. During viewing of foodrelated stimuli, leptin replacement reduced brain activation in regions linked to hunger (insula, parietal and temporal cortex) while enhancing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
157
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(168 citation statements)
references
References 28 publications
7
157
0
4
Order By: Relevance
“…Imaging studies reported activation of the somatosensory cortex in normal weight subjects with exposure to visual images of low caloric foods (Killgore et al, 2003) and with satiety (Tataranni et al, 1999), and we had shown higher than normal baseline metabolism in the somatosensory cortex in obese subjects (Wang et al, 2002). Also a recent study reported that in obese individuals with leptin deficiency administration of leptin normalized their body weight and reduced brain activation in parietal cortex while viewing food-related stimuli (Baicy et al, 2007). The functional connectivity between the striatum and the somatosensory cortex was recently corroborated for the human brain by a meta-analysis study on 126 functional imaging studies, which documented coactivation of the somatosensory cortex with that of the dorsal striatum (Postuma and Dagher, 2006).…”
Section: Correlation Between D2r and Somatosensory Cortexsupporting
confidence: 60%
“…Imaging studies reported activation of the somatosensory cortex in normal weight subjects with exposure to visual images of low caloric foods (Killgore et al, 2003) and with satiety (Tataranni et al, 1999), and we had shown higher than normal baseline metabolism in the somatosensory cortex in obese subjects (Wang et al, 2002). Also a recent study reported that in obese individuals with leptin deficiency administration of leptin normalized their body weight and reduced brain activation in parietal cortex while viewing food-related stimuli (Baicy et al, 2007). The functional connectivity between the striatum and the somatosensory cortex was recently corroborated for the human brain by a meta-analysis study on 126 functional imaging studies, which documented coactivation of the somatosensory cortex with that of the dorsal striatum (Postuma and Dagher, 2006).…”
Section: Correlation Between D2r and Somatosensory Cortexsupporting
confidence: 60%
“…Therefore, there is increasing evidence of importance of leptin in processing food stimuli. 21 Evidence of hippocampal involvement in food-related behaviors has also been reported. To start with, the neuroanatomical connections of the hippocampus allow it to receive information from areas of the brain involved in satiety and hunger signals including the arcuate nucleus in the hypothalamus, 22 the nucleus tractus solitarius, which receives afferents from the vagus 23 that are thought to regulate food intake 24 and from the insula, which processes internal perception of hunger signals 25 and in concert with the hippocampus is thought to be involved in novel taste learning.…”
Section: Discussionmentioning
confidence: 93%
“…One of the most important adipokines, leptin, has been implicated in a variety of functions of the central nervous system such as learning and memory processes, neuroendocrine regulation, and possibly neuroprotection [17][18][19][20]. Leptin replacement in genetically leptin-deficient adults modulates the sensitivity to visual food stimuli, with reduced activation in hunger related areas and enhanced response in regions involved in satiation [21,22]. Likewise, metabolic factors such as glucose and free fatty acids (FFA) are likely to serve as regional modulators of postprandial neuronal events [23].…”
Section: Introductionmentioning
confidence: 99%